The infrastructure of the third sector of the Republic of Kazakhstan: internal and external environment (The Journal of Psychology and Sociology, 2012)
The article studies the internal and external environment of NGOs forming the infrastructure of the third sector. As follows from the basic provisions of organizational unity and following the main mission of the target organization determines the efﬁ ciency and professionalism of the team leaders.
Keywords: NGO; external environment; professionalism; the efﬁ ciency.